A review of non-destructive testing techniques for the in-situ investigation of fretting fatigue cracks. (November 2020) - Kong, Y.; Bennett, C.J.; Hyde, C.J.
Abstract: Fretting fatigue can significantly reduce the life of components, leading to unexpected in-service failures. This phenomenon has been studied for over a century, with significant progress being made during the past decade. There are various methods that have been used to study fretting fatigue cracks in order to gain a greater understanding of the effects of fretting fatigue. Destructive methods are traditionally used to observe fretting fatigue cracks. Although useful in determining crack location, crack length, crack propagation modes, crack path and shape, it is not efficient or reliable for time based measurements. Non-destructive testing has developed in recent years and now in-situ monitoring can be used during testing in order to increase the understanding of fretting fatigue. This paper presents a review of non-destructive testing techniques used in-situ during fretting fatigue testing, which are compared in order to conclude the suitability of each technique. Recent developments in non-destructive techniques that could be also applied for fretting fatigue tests are also discussed, as well as recommendations for future research made. Graphical abstract: Unlabelled Image Highlights: A review on recent non-destructive techniques that have been used in-situ with fretting fatigue tests for crack detection. Comparisons of the sensitivity, the number of cycles to crack nucleation detection and capability of techniques. Recent developments in non-destructive techniques applicable to fretting fatigue.